2017
DOI: 10.23846/egm007
|View full text |Cite
|
Sign up to set email alerts
|

State-society relations in low- and middle-income countries: an evidence gap map

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, for whom, why and at what cost. We believe that high-quality and policyrelevant evidence will make development more effective and improve people's lives. 3ie evidence gap maps 3ie evidence gap maps (EGMs) are thematic collections of information about impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 13 publications
(20 reference statements)
0
42
0
Order By: Relevance
“…The review used the evidence gap map of state-society relations as a primary source of potential studies (Phillips et al, 2017). In addition, authors screened the bibliography of existing systematic reviews and literature reviews, including Molina et al, (2016), Lynch et al (2013) and Hanna et al (2011).…”
Section: Other Searchesmentioning
confidence: 99%
“…The review used the evidence gap map of state-society relations as a primary source of potential studies (Phillips et al, 2017). In addition, authors screened the bibliography of existing systematic reviews and literature reviews, including Molina et al, (2016), Lynch et al (2013) and Hanna et al (2011).…”
Section: Other Searchesmentioning
confidence: 99%
“…A recent evidence gap map (EGM) on "state-society relations" highlighted a number of interventions to improve governance (Phillips et al, 2017). These were broadly grouped into interventions for inclusive political processes and leadership (e.g.…”
Section: The Universe Of Interventions Promoting Pita Mechanismsmentioning
confidence: 99%
“…Drawing on Phillips et al (2017), as well as insights from the literature, we theorized good governance can come about through sustained improvements across three domains: within the political system; within the management and administration of public sector offices and institutions; and in the ways in which public officials and service providers engage with service users (external engagement) (Waddington et al, 2018). In this framing, good governance interventions attempt to influence the social contract that mediates the relationships between government and citizens, regarding who has access to what power and in return for what accountability for service provision, through the three domains:…”
Section: The Universe Of Interventions Promoting Pita Mechanismsmentioning
confidence: 99%
“…Drawing on Phillips et al (2017), and also insights from the literature, we theorise good governance can come about through sustained improvements across three domains: within the political system; within the management and administration of public sector offices and institutions; and in the ways in which public officials and service providers engage with service users (external engagement). In this framing, good governance interventions attempt to influence the social contract that mediates the relationships between government and citizens, regarding who has access to what power and in return for what accountability for service provision, through three accountability domains: Influencing how the broader political system functions: The broader political system dictates access to and contestability of the policy arena (World Bank, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence gap map on interventions to improve state‐society relations concluded that there are few systematic reviews on governance topics, and many of those that are available are out‐dated or of low quality in terms of the methodology they employ (Phillips et al, 2017). Phillips et al identify several high‐quality existing systematic reviews that cover evidence that is relevant to the substantive scope of this review.…”
Section: Introductionmentioning
confidence: 99%